Multiple roles of Spo11 in meiotic chromosome behavior - Celerin, Martina (Oxford University Press, 2000)
Spo11, a type II topoisomerase, is likely to be required universally for initiation of meiotic recombination. However, a dichotomy exists between budding yeast and the animals Caenorhabditis elegans and Drosophila melanogaster with respect to additional roles of Spo11 in meiosis. In Saccharomyces cerevisiae, Spo11 is required for homolog pairing, as well as axial element (AE) and synaptonemal complex (SC) formation. All of these functions are Spo11 independent in C.elegans and D.melanogaster. We examined Spo11 function in a multicellular fungus, Coprinus cinereus. The C.cinereus spo11-1 mutant shows high levels of homolog pairing and occasionally forms full-length AEs, but no SC. In C.cinereus, Spo11 is also required for maintenance of meiotic chromosome condensation and proper spindle formation. Meiotic progression in spo11-1 is aberrant; late in meiosis basidia undergo programmed cell death (PCD). To our knowledge, this is the first example of meiotic PCD outside the animal kingdom. Ionizing radiation can partially rescue spo11-1 for both AE and SC formation and viable spore production, suggesting that the double-strand break function of Spo11 is conserved and is required for these functions.